2008
DOI: 10.1523/jneurosci.2623-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Fear Conditioning and Extinction Differentially Modify the Intrinsic Excitability of Infralimbic Neurons

Abstract: Extinction of conditioned fear is an active learning process involving inhibition of fear expression. It has been proposed that fear extinction potentiates neurons in the infralimbic (IL) prefrontal cortex, but the cellular mechanisms underlying this potentiation remain unknown. It is also not known whether this potentiation occurs locally in IL neurons as opposed to IL afferents. To determine whether extinction enhances the intrinsic excitability of IL pyramidal neurons in layers II/III and V, we performed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
273
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(303 citation statements)
references
References 71 publications
27
273
3
Order By: Relevance
“…Thus, following learning, hippocampal neurons may express BDNF initially, followed by BDNF expression in hippocampal targets such as mPFC and amygdala. Increased excitability in IL following extinction has been shown to predict extinction success (Burgos-Robles et al, 2007;Chang et al, 2010;Knapska and Maren, 2009;Santini et al, 2008). We observed that infusing BDNF into vHPC increased the firing rate of IL neurons, a vHPC target.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, following learning, hippocampal neurons may express BDNF initially, followed by BDNF expression in hippocampal targets such as mPFC and amygdala. Increased excitability in IL following extinction has been shown to predict extinction success (Burgos-Robles et al, 2007;Chang et al, 2010;Knapska and Maren, 2009;Santini et al, 2008). We observed that infusing BDNF into vHPC increased the firing rate of IL neurons, a vHPC target.…”
Section: Discussionmentioning
confidence: 71%
“…Although the present experiments focused primarily on the prelimbic (PLC) division of the mPFC, during the acquisition and expression (recall) phases of emotional associative memory, considerable evidence points to a functional dissociation between the prelimbic and infralimbic divisions of the mPFC during the acquisition versus extinction of emotional memory (Quirk and Mueller, 2008;Santini et al, 2008), such that neurons within the PLC appear critical for emotional memory acquisition whereas infralimbic neurons appear critical for extinction-related learning. The present results, although not directly examining the role of the infralimbic cortex in DA-related emotional memory acquisition and recall, also demonstrate an important role for the PLC in the encoding phase of emotional associative memory.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological blockade of CB1 abolished these effects. This is a striking observation, since the infralimbic cortex undergoes plastic changes during relearning/extinction training (Santini et al, 2008), which are thought to underlie its subsequent involvement in suppression of conditioned fear during extinction recall (Milad and Quirk, 2002). However, in light of the largely intact between-session extinction observed in mice with pharmacological blockade of CB1 (Fig.…”
Section: Discussionmentioning
confidence: 97%